From judge to constituent: the court of justice and the constitutional transformation of the European Union - Neves Pérez, Hugo (2025)
This article analyzes the process of constitutionalization of the European Union in the absence of a formal Constitution, focusing on the role of the Court of Justice of the European Union as a de facto constituent power. Through the study of both foundational and recent case law, it is demonstrated that the court has progressively built a normative order with constitutional features, based on principles such as primacy, direct effect, the autonomy of EU law, the protection of fundamental rights, and the values enshrined in Article 2 of the Treaty on European Union. The article also examines the conflicts between the Court of Justice of the European Union and various national constitutional courts (notably those of Germany, Poland, and Spain), which illustrate the tension between European legal unity and internal constitutional pluralism. Finally, it reflects on the viability of a future formal Constitution for the EU and defends the thesis that, in the absence of such a text, European constitutionalism is expressed in a functional, material, and judicially consolidated form-albeit not without challenges in terms of democratic legitimacy and institutional cohesion.